Metode Drilling dalam Peningkatan Kemampuan Motorik Halus Anak Usia Dini di sekolah TK - hariry, hamdan (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the implementation of the drilling method and its effectiveness in learning at the kindergarten level. The drilling method or repeated practice is often used at this educational level, especially to introduce basic concepts such as letters, numbers, and shapes, as well as to train fine and gross motor skills. A descriptive qualitative approach was used in this study, involving direct observation of teaching and learning activities and in-depth interviews with kindergarten teachers in the selected sample schools. The results showed that teachers implemented drilling through various interesting and varied activities, such as the habit of daily prayers, memorizing short letters, learning in the form of games, and simple drawing. The application of this drilling method has proven effective in helping children to strengthen memory and internalize concepts quickly. However, it is important to note that the success of this method depends heavily on the teacher’s creativity in combining it with other play methods so that the learning process does not feel monotonous and remains enjoyable for children. The conclusion of this study emphasizes the need for a balance between drilling and play-based activities to optimize the cognitive and psychological development of early childhood.